The role of entirely subcutaneous ICD™ systems in patients with dilated cardiomyopathy. Issue 5 (May 2020) - Willy, Kevin; Reinke, Florian; Bögeholz, Nils; Ellermann, Christian; Rath, Benjamin; Köbe, Julia; Eckardt, Lars; Frommeyer, Gerrit
Highlights: The S-ICD system is a feasible alternative to transvenous ICDs in patients with DCM. Ventricular arrhythmias are effectively terminated by the S-ICD. In particular in young patients with DCM S-ICD implantation should be preferred. Abstract: Background: The subcutaneous implantable-cardioverter defibrillator (S-ICD™, Boston Scientific, Natick, MA, USA) is an important advance in device therapy for the prevention of sudden cardiac death (SCD). Although current guidelines recommend S-ICD™ use, long-term data are still limited, especially in subgroups. Dilated cardiomyopathy (DCM) is a common reason for the implantation of an ICD. However, there are no sufficient data on the performance of the S-ICD™ in this patient cohort. Materials and methods: All S-ICD™ patients with DCM as the main indication for ICD implantation (n = 47 patients) in our large-scaled single-center S-ICD™ registry (n = 294 patients) were included in this study. Baseline characteristics, appropriate and inappropriate shocks, and complications were documented in a mean follow-up of 22.9 ± 18.5 months. Results: A total of 47 patients with DCM as the underlying structural heart disease received an S-ICD™ in our institution. Mean left ventricular ejection fraction was 37 ± 12% and a 28% had a history of ventricular tachyarrhythmia. During follow-up eight ventricular tachyarrhythmias were adequately terminated in three patients. In four patients, oversensing resulting in an inappropriate shock was observed, which could be managed by changing the sensing vector. There was no need for a change to a cardiac resynchronization (CRT) system while one system was changed to a VVI-ICD due to S-ICD™ wound infection. Conclusion: The S-ICD™ seems to be a valuable option for the prevention of SCD in patients with DCM and no indication for CRT. As clinically relevant ventricular arrhythmias consisted of ventricular fibrillation or fast ventricular tachycardia in all patients in our cohort, no change to transvenous ICDs for anti-tachycardia pacing delivery was necessary.